Šport in UV-sevanje - Hadžić, Vedran (Šport (Ljubljana), 2025)
Overexposure to UV radiation during exercise can significantly increase the risk of skin cancer in competitive and recreational athletes. For the former, the risk is further increased due to higher and longer sun exposure. Preventive measures include, in particular, the use of protective creams and clothing (shirts and caps), the use of sunglasses and other general measures such as regular self-examinations of the skin. Despite the fact that most people are aware of the dangers of UV radiation, there is a problem at the level of the implementation of preventive measures, and future educational campaigns should focus on this area.
Keywords: kožni rak; malignant melanoma; maligni melanom; physical activity; skin cancer; sport; sun proteciton; šport; telesna dejavnoat; zaščita pred soncem